Image Schema in Imam Ali's Morning Supplication "Dua Isabah" - Abbas Sultan; Fayhaa Alsabbagh (آداب الكوفة, 2021)
This study deals with the imaginary schema of Mark Johnson, 1987)) in the morning prayer, which are organized structures in human cognitive perception, which arise from physical and social interaction with the external world at the perceptual level. On this basis, it is considered the main essence ofs